Microbial safety and sensory quality of instant low-salt Chinese paocai. (January 2016) - Zhang, Qisheng; Chen, Gong; Shen, Wenxi; Wang, Yong; Zhang, Wenxue; Chi, Yuanlong
Abstract: Paocais with low-salt (1–3% NaCl), medium-salt (4–5% NaCl) and high-salt (10% NaCl) were prepared, and four food-borne pathogens were separately inoculated at the initial stage of paocai fermentation. The changes in pH and titratable acidity were determined. The antagonistic effects of lactic acid bacteria (LAB) on these four pathogens were studied, and the antimicrobial substances in paocai brines were analyzed. Furthermore, the sensory characteristics of paocais were evaluated. Compared to medium-salt and high-salt paocais, low-salt paocai showed a shorter ripening period. The LAB exhibited a high growth rate in low-salt paocai, and the pathogens achieved 5-log reduction within 4 days of fermentation, which suggests that low-salt paocai has a good microbial safety. The antagonism of LAB toward these pathogens was confirmed by antimicrobial substances including organic acids and bacteriocins. Besides, the low-salt paocai has acceptable sensory quality. Highlights: LAB had antagonistic effects on four food-borne pathogens tested in paocai brine. Antimicrobial substances in paocai were identified as organic acid and bacteriocin. Low-salt paocai exhibited a good microbial safety in short-term fermentation. Low-salt paocai has acceptable sensory quality.